A Novel Bipolar Polypectomy Snare Can Be an Alternative Choice for Endoscopic Resection - Chen, Shengsen; Zhou, Danping; Ruan, Rongwei; Yu, Jiangping; Li, Yandong; Liu, Yuanshun; Wang, Shi (Frontiers in Medicine, 2021)
Objective: Endoscopic resection(ER) is more difficult and has a higher rate of complications, such as perforation and bleeding. The aim of this study was to evaluate the safety and feasibility of a bipolar polypectomy snare for ER. Methods: Initial ER procedures in live pigs was carried out. Then a human feasibility study was performed in patients with colorectal polyps. Finally, the finite element method was used to evaluate the safety and effectiveness of the new bipolar snare. Results: In the live animal model, there were no significant differences in wound size and cutting time between monopolar and bipolar groups. The histological results (histological scores) of the two groups in porcine experiments were almost same except that the incision flatness of bipolar group was better than that of monopolar group. Incidence of bleeding and perforation was similar between the two groups in pigs’ and patients’ study. At last, the finite element model showed that the vertical thermal damage depth produced by bipolar snare system was about 71% -76% of that produced by monopolar snare system at the same power. Conclusions: The novel bipolar snare is feasible in patients with colorectal polyps, and can be an alternative choice for endoscopic resections.